Cation ordered Ni-rich layered cathode for ultra-long battery life. Issue 3 (22nd February 2021) - Kim, Un-Hyuck; Park, Geon-Tae; Conlin, Patrick; Ashburn, Nickolas; Cho, Kyeongjae; Yu, Young-Sang; Shapiro, David A.; Maglia, Filippo; Kim, Sung-Jin; Lamp, Peter; Yoon, Chong S.; Sun, Yang-Kook
Abstract : The observed ultra-long battery life of 8000 cycles demonstrated by the Ni-rich compositionally graded NCM cathode stems mainly from the cation ordered structure. Abstract : Fluorine doping of a compositionally graded cathode, with an average concentration of Li[Ni0.80 Co0.05 Mn0.15 ]O2, yields a high discharge capacity of 216 mA h g −1 with unprecedented cycling stability by retaining 78% of its initial capacity after 8000 cycles. The cathode is cycled at 100% depth of discharge (DOD), unlike the currently deployed layered cathode whose DOD is limited to 60–80% to compensate for capacity fading and guarantee the required battery life. Additionally, the capacity and cycling stability of the cathode easily surpass those of the existing state-of-the-art batteries, while achieving the energy density goal of 800 W h kg −1 cathode for electric vehicles (EV) with ultra-long cycle life. The structural and chemical stabilities of the cathode were provided by the compositional partitioning and unique microstructure of the compositionally graded cathode combined with the ordered site-intermixing of Li and transition metal (TM) ions discovered via transmission electron microscopy. F doping induced the formation of a 2 a hex × 2 a hex × c hex superlattice from ordered Li occupation in TM slabs and vice versa, which has been proven to be essential for suppressing microcrack formation in deeply charged states, while maintaining the structural stability of the cathode during extended cycling. Furthermore, the proposed cathode allows for the recycling of used EV batteries in energy storage systems, thereby alleviating the negative environmental impact by reducing the CO2 emissions and cost associated with disposing of dead batteries.